EXPERT INFORMATION-ANALYTICAL SYSTEM AS A METHOD OF STRATEGIC MANAGEMENT OF THE PROCESS OF PSYCHOLOGICAL PREPARATION IN SPORTS - Banayan A.A. ,; Malinin A.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop the structure of an expert information-analytical system for the psychological support of athletes. Methods and structure of the study. The development was carried out at the Saint-Petersburg scientific-research institute for physical culture. The tasks to be solved by the expert information-analytical system (EIAS) are defined: a combined monitoring method that allows offline and online testing; drawing up a unified form of conclusions and recommendations; automatic statistical processing with subsequent interpretation of the data according to the specified parameters. Results and conclusions. The developed system is multifunctional and is focused on collecting various kinds of characteristics for three types of personal status, namely, an athlete, coach, sports referee, which will allow the following in the future: to form a personal card in the library for each segment of the audience; identify the ratio and prevalence of certain sports depending on the subject of the Russian Federation; specify the number of physical culture and sports organizations that provide services to the population on a reimbursable and non-reimbursable basis and have staff in the position of sports psychologist; determine the course of implementation of the regulatory requirements of the Federal Standard for Sports Training (FSST), which regulate the process of psychological support, corresponding to reality; develop a professional standard in sports psychology; make scientifically sound proposals on the content, volume and types of psychological training in the existing FSST.